2013
DOI: 10.1111/myc.12141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and epidemiological characteristics of vaginal candidiasis in the UAE

Abstract: Vaginal candidiasis (VC) continues to be a health problem to women worldwide. Although the majority of VC cases are caused by Candida albicans (C. albicans), non-albicans Candida spp. like C. glabrata and C. tropicalis are emerging as important and potentially resistant opportunistic agents of VC. The objective of this study was to evaluate the prevalence and epidemiology of VC in the UAE through retrospective analysis of pertinent data compiled by the microbiology and infection control unit at Latifa Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
5
17
0
3
Order By: Relevance
“…There is need to draw the attention of clinicians in our environment to this situation so that they can sought improve treatment via different approaches, which may include the combination (synergistic) of antifungals as evidence has shown that combinatory therapy contributes to reducing toxicity and could be an alternative for treatment of candidiasis due to C. albicans [58,59]. However, the possibility of some system bias cannot be excluded due to the potential reasons of the different specimen, test method, and regional disparity [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…There is need to draw the attention of clinicians in our environment to this situation so that they can sought improve treatment via different approaches, which may include the combination (synergistic) of antifungals as evidence has shown that combinatory therapy contributes to reducing toxicity and could be an alternative for treatment of candidiasis due to C. albicans [58,59]. However, the possibility of some system bias cannot be excluded due to the potential reasons of the different specimen, test method, and regional disparity [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Often, prolonged antifungal regimens or alternative treatment approaches (e.g., vaginal boric acid suppositories) are required for clearance [24,25]. Given reduced therapeutic efficacy, recent reports suggesting increased incidence rates of NAC-associated VVC are somewhat unsettling [26,27]. However, such reports should be taken with caution, as symptomatic VVC can mimic several disease states of the lower FRT and the ability to distinguish Candida as a true pathogen from an asymptomatic colonizer can be difficult.…”
Section: Pathology and Epidemiology Of Vulvovaginal Candidiasismentioning
confidence: 99%
“…Rathod et al [123] expressed doubts on the often quoted figures in various publications, and contended that these are higher than the true magnitude of the problem [123]. Recent reports though indicate that the incidence of genital candidiasis is increasing [124]. Cognisant of global increases in some of the key risk factors thereof, such as diabetes mellitus, antibiotic use, and changing individual life-styles and more liberal sexual behaviours and practices which may increase the risk thereto, this assertion may not be far-fetched.…”
Section: Discussionmentioning
confidence: 95%